2020
DOI: 10.1159/000511242
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, Trend and Predictors of Adult-Onset Type 1 Diabetes in Uyo, Nigeria

Abstract: <b><i>Background:</i></b> Unlike what obtains in childhood-onset type 1 diabetes, there remains a paucity of data on adult-onset type 1 diabetes in Nigeria. Hence, the current study aimed to determine the general characteristics of adult-onset type 1 diabetes among subjects (aged ≥18 years) presenting at the University of Uyo Teaching Hospital (UUTH) in Akwa Ibom State, South-south Nigeria. <b><i>Methods:</i></b> A 5-year (2014–2018) retrospective records review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Higher educational status was another demographic characteristic associated with T1DM at Ayobo Primary Health Center. This finding is consistent with the findings of Amadi et al (2020) in Uyo, Nigeria, and Olssen et al (2011) in the Nord-Trøndelag Health Study. Ogundele et al (2016) also reported the preponderance of individuals with higher education among diabetics in Lagos.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Higher educational status was another demographic characteristic associated with T1DM at Ayobo Primary Health Center. This finding is consistent with the findings of Amadi et al (2020) in Uyo, Nigeria, and Olssen et al (2011) in the Nord-Trøndelag Health Study. Ogundele et al (2016) also reported the preponderance of individuals with higher education among diabetics in Lagos.…”
Section: Resultssupporting
confidence: 91%
“…Unfortunately, there was not enough information to ascertain if the diabetic adults had adult-onset T1DM or childhood-onset T1DM and survived to adulthood. However, some studies carried out in Africa, including Padoa (2011), Amadi et al (2020), andBalcha et al (2020), have reported the preponderance of adult-onset T1DM on the continent. Adewumi et al (2022) also found that the majority of individuals with either type 1 or type 2 diabetes mellitus in Lagos were between the ages of 41 and 60.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding residence, urban dwellers had a lower risk (40%) of DKA as compared to rural dwellers. This study is in line with a study conducted in Nigeria [23], and Hawassa Comprehensive Specialized Hospitall [17]. On the contrary, a study done in Australia and New Zealand [33,34] revealed that rural dwellers were at higher risk of DKA than urban dwellers.…”
Section: Discussionsupporting
confidence: 90%
“…In 2015, the estimated cost of DM in sub-Saharan Africa was about $19.45 billion [22]. Age and urban residence were identified as sociodemographic predictors of DKA [17,23,24]. Besides the above, T1D, the presence of comorbidity, infection prior to the onset of DKA, poor glycemic control, and medication discontinuation are associated with DKA [25][26][27].…”
Section: Introductionmentioning
confidence: 99%